N,N′-tetrasubstituted succinamides as new molecules for liquid–liquid extraction of Pt(IV) from chloride media - Costa, Maria Clara (2016)
Due to the increasing demand of platinum group metals (PGM’s), among which platinum, the search for new alternatives aiming to their extraction and recovery is nowadays of great importance. Thus, two N, N0-tetrasubstituted succinamides, N,N0-dicyclohexyl-N,N0-dimethylsuccinamide (DMDCHSA) and N,N0- dimethyl-N,N0-diphenylsuccinamide (DMDPHSA) were synthesized and investigated, for the first time, as potential molecules for the liquid–liquid extraction of Pt(IV) from chloride solutions. According to the extraction and stripping results obtained in a single contact, these succinamides can be considered promising extractants for the recovery of platinum(IV) from hydrochloric acid media, since DMDCHSA is able to extract more than 95% Pt(IV) from 4 M HCl or higher concentrations, and DMDPHSA extracts 80% and 92% Pt(IV) from 6 M and 8 M HCl solutions, respectively. Furthermore, platinum(IV) can successfully be stripped through a simple contact with seawater: 93% Pt(IV) were recovered from DMDCHSA, while 60% stripping were obtained from DMDPHSA. For each compound, the time necessary to reach equilibrium, and the effects of the type of diluent and different extractant concentrations on the Pt(IV) extraction percentage were investigated. The loading capacity of DMDCHSA and DMDPHSA toward Pt (IV) was also evaluated, and the results show that both extractants present a very high loading capacity. In addition, data obtained from successive extraction-stripping cycles suggest a good stability pattern for both succinamides.